Pendampingan mahasiswa - Chalik, Citra Aulian; Bakri, Suriyanto; Muhamad Hardin Wakila; Mubdiana Arifin (Kilau Publishing, 2023)
The Teaching Campus Program is a program to increase literacy and numeracy for students in target schools. In this program, students at tertiary institutions can contribute to helping the government in increasing literacy and numeracy. Students can study outside campus to improve soft skills, creativity, and leadership in running campus teaching programs. In this activity, lecturers at universities can accompany students as a form of community service and help in improving the quality of basic education in Indonesia. SMP Negeri 28 Makassar is one of the target schools for the Batch 4 campus teaching program. A total of 4 students were assigned to SMP Negeri 28 Makassar. Field Supervisor Lecturers (DPL) as companions for Batch 4 Campus Teaching Program (PKM) students at SMP Negeri 28 Makassar provide direction and guidance in carrying out activity programs. The results of PKM student mentoring activities increase students' ability to solve problems and run the program well. This PKM mentoring is a contribution of university lecturers in serving the community and improving lecturer performance.